The Knowledge Enhancement of Stunted Children’s Parentals Through Training on Processing Additional Foods with White Oyster Mushroom, Taro Flour, and Fish Raw Materials - bakara, tiar lince; Rumida; Siahaan, Ginta (Talenta Publisher Universitas Sumatera Utara, 2022)
The problem of malnutrition that has received much attention recently is the problem of chronic nutrition in the form of stunting. One of the factors that cause stunting in toddlers is food intake. The provision of supplementary food containing complete nutrition can be used as an effort to prevent stunting in children. This community service was carried out in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency with the target community being the PKK Cadre group and mothers with stunting children. The purpose of this community service activity is to convey information about stunting children and how to prevent it, as well as train the target community to utilize and process food ingredients such as white oyster mushrooms, taro flour, catfish, rebon shrimp and lemuru fish into nuggets as a snack for children. stunting. The results of community service activities showed an increase in the participants' knowledge about stunting and how to prevent it, as well as skills to make catfish, rebon shrimp, lemuru fish, and oyster mushroom nuggets as snacks for stunted children.